RANCANG BANGUN SISTEM INFORMASI GEOGRAFI BERBASIS ANDROID PEMETAAN FASILITAS AUTOMATED TELLER MACHINE MENGGUNAKAN GOOGLE MAPS API DAN METODE UJI PRODUK ISO 9126 - Yosef Murya Kusuma Ardhana (JURNAL INFORMATIKA DAN KOMPUTER, 2017)
The aim of this study was to design geographic information system based on Android. This would be used to map the ATM machines in Yogyakarta in which later on could help people to search the address or the geographic location of the ATM machines. The researcher used Java and XML program in developing the geographic information system. Java was used to build the system, and XML was used to build user interface or display interface. On the other hand, data base which was used in this study was MySQL.The system development methodology used in this study was Waterfall methodology. This methodology had some steps, they are analysis, design, implementation, testing, and maintenance. In data collecting process, the researcher used observation, interview, and literature methods. Output which would be produced in developing geographic information system was an application of Geographic Information System mapping ATM machine facilities.The application of Geographic Information System mapping ATM machine facilities was tested using product testing methodology ISO 9126. The scores were > 3.0 to each criteria from ISO 9126. The functionality score was 4,24. The reliability score was 4,27. The usability score was 4,42, and the efficiency score was 4,61. Therefore, the application of Geographic Information System mapping ATM machine facilities could fulfil the need of ATM machine userKeywords : Geographic Information System, ISO 9126, Google Maps, Android, Waterfall